(untitled) (Physical Education, Health and Social Sciences, 2025)
Objectives: This study initiated to develop communication books using core vocabulary of Urdu language. Communication book is an Augmentative Communication (AAC) device that is of great help for SLP’s while dealing with special children. This study is aimed to use the Urdu core vocabulary words and pictures that describe the words accurately. Materials and Methods: Age range for which the book needs to be developed was 4 to 5 years. The initial step is to identify the core vocabulary of Urdu language. This was done by using Urdu books of age range 4 to 5 years. Language of children of 4 to 5 years of age was observed very carefully. This helped in modifying the core vocabulary list. Pictures related to the core words were formulated. The final list and pictures were finalized with help of Speech and language Pathologists. Results: Item Content Validity Index (I-CVI) was calculated for expert review. I-CVI defined the appropriateness of words and pictures. For piloting typically developing children (N=16) were recruited which include genders were recruited (boys = 8, girls=8). Age range was between 4 to 5 years. Mean age was 1.50 and S.D was .516. Children were shown pictures and for every correct response were rated on the checklist. Their responses were entered in SPSS-20. Frequency and Percentage were calculated. Conclusion: Most of the words have percentage frequency more than 80. All the pictures and words were appropriate and were used in developing Communication Book. Implication for Rehabilitation: Developed books will be used as assessment and also as treatment purpose.